Peningkatan Peran Dan Fungsi Keluarga Dalam Mengatasi Bullying Melalui Konseling Keluarga Di Mesjid Nurush Sadri Kota Pekanbaru - Muhsin Tampubolon, Sintong; Elmirawati, Elmirawati; Habibah, Ummi; Syawitri, Melsy; Asmidaryani, Asmidaryani (Al-Umm: Jurnal Pengabdian dan Pengembangan Masyarakat, 2024)
The aim of providing information services about bullying at the Nurush Sadri Mosque, Pekanbaru City is to increase public knowledge and understanding regarding bullying and understand strategies for preventing and handling bullying. The aim of this service is to provide the community with a proper and better understanding about bullying, forms of bullying, and the impact of bullying, as well as how to react to bullying behavior. There were 42 participants who took part in this activity. The results of the service showed that the participants' level of understanding increased significantly after participating in the activity. Specifically, regarding what is meant by bullying, how to avoid bullying, and how to behave towards bullies